Gold(I)-catalyzed hydroaminaloxylation and petasis-ferrier rearrangement cascade of aminaloalkynes - Gade, Amol B.; Patil, Nitin T. (Organic Letters, 2016)
An efficient method has been developed to generate a diverse array of indolizidines and quinolizidines from readily available aminaloalkynes via a gold(I)-catalyzed hydroaminaloxylation and Petasis-Ferrier rearrangement cascade. The method enabled a formal synthesis of (+/-)-antofine.

[3+2]-Annulation of platinum-bound azomethine ylides with distal C[double bond, length as m-dash]C bonds of N-allenamides - Chakrabarty, Indradweep; Inamdar, Suleman M.; Akram, Manjur O.; Gade, Amol B.; Banerjee, Subhrashis; Bera, Saibal; Patil, Nitin T. (Chemical Communications, 2017)
A Pt-catalyzed, highly regioselective reaction between N-allenamides and imino-alkynes leading to pyrrolo[1,2-a] indoles is described. This represents the first example of [3+2]-annulation of Pt-bound azomethine ylides with the distal CQC bond of N-allenamides. The mechanism of the reaction was established by computational studies.

Catalytic enantioselective aza-piancatelli rearrangement - Gade, Amol B.; Patil, Nitin T. (Synlett, 2017)
The design and development of an enantioselective aza-Piancatelli rearrangement reaction are described. In the presence of a chiral phosphoric acid catalyst, furylcarbinols react with anilines to afford highly functionalized cyclopentenones with excellent diastereo-and enantioselectivities. The process was shown to be scalable, and up to 1 gram of starting material could be employed under mild reaction conditions.

Catalytic enantioselective 1,3-alkyl shift in alkyl aryl ethers: efficient synthesis of optically active 3,3 '-diaryloxindoles - Gade, Amol B.; Bagle, Pradip N.; Shinde, Popat S.; Bhardwaj, Vipin; Banerjee, Subhrashis; Chande, Ajit; Patil, Nitin T. (Angewandte Chemie-International Edition, 2018)
Reported is the first organocatalytic asymmetric 1,3-alkyl shift in alkyl aryl ethers for the synthesis of chiral 3,3'-diaryloxindoles using a chiral Bronsted acid catalyst. Preliminary results showed that each enantiomer of the 3,3'-diaryloxindole, and a racemic mixture, showed different antiproliferative activities against HeLa cell lines by using an MTT assay.

A new class of N-doped ionic PAHs via intramolecular [4+2]-cycloaddition between arylpyridines and alkynes - Mule, Ravindra D.; Shaikh, Aslam C.; Gade, Amol B.; Patil, Nitin T. (Chemical Communications, 2018)
Reported herein, for the first time, is a copper-promoted intramolecular [4+2]-cycloaddition cascade to access ionic N-doped polycyclic aromatic hydrocarbons (PAHs) with tunable emission wavelengths. It is shown that the reaction can be made catalytic with respect to Cu(OTf)(2) when an external oxidant, Selectfluor, was used.

Gold(I)-catalyzed hydroxy group assisted C(sp(2))-H alkylation of enaminones with diazo compounds to access 3-alkyl chromones - Bagle, Pradip N.; Mane, Manoj V.; Sancheti, Shashank P.; Gade, Amol B.; Shaikh, Samir R.; Baik, Mu-Hyun; Patil, Nitin T. (Organic Letters, 2019)
A strategy for expedient synthesis of 3-substituted chromones from easily available o-hydroxyarylenaminones and diazo compounds has been developed. Carefully conducted experimental and computational studies led us to propose an uncommon mechanistic pathway involving the hydroxyl group assisted alkylation of enaminones with in situ generated gold carbenes.